2005
DOI: 10.1002/ffj.1622
|View full text |Cite
|
Sign up to set email alerts
|

Production of flavour precursors byPenicilliumcandidum using selected polyunsaturated fatty acids

Abstract: Biomass of Penicillium candidum was harvested and homogenized prior to centrifugation. The resultant supernatant, considered as the crude enzymatic extract, was enriched by ammonium sulphate precipitation. The enriched enzymatic extract was assayed for its lipoxygenase (LOX) activity, using selected polyunsaturated fatty acids (PUFAs) as substrates. Two pH optima for LOX activity were determined at 6.0 and 8.5. The results indicated a wide range of LOX activity towards free PUFAs, including linoleic, linolenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Kuribayash et al (2002) also reported that the Km and Vmax of LOX from Pleurotus ostreatus were 0.13 mM and 23.4 µmol/min/mg, respectively. However, soybean LOX-1 Km was 0.02 mM (Hall et al, 2004), while for canola seed (0.2 mM) (Khalyfa et al, 1990), for tomato 0.52 mM (Todd, et al, 1990), for a land plant Phaseolus vulgaris L. it was 1.4 mM (Sicilia, et al, 2005), and 2.8 mM for broad bean (Al-Obaidy and Siddioi,1981). Polyacrylamide gel electrophoresis in the presence of a surfactant SDS produced a single protein band as represented on Figure 9.…”
Section: Resultsmentioning
confidence: 99%
“…Kuribayash et al (2002) also reported that the Km and Vmax of LOX from Pleurotus ostreatus were 0.13 mM and 23.4 µmol/min/mg, respectively. However, soybean LOX-1 Km was 0.02 mM (Hall et al, 2004), while for canola seed (0.2 mM) (Khalyfa et al, 1990), for tomato 0.52 mM (Todd, et al, 1990), for a land plant Phaseolus vulgaris L. it was 1.4 mM (Sicilia, et al, 2005), and 2.8 mM for broad bean (Al-Obaidy and Siddioi,1981). Polyacrylamide gel electrophoresis in the presence of a surfactant SDS produced a single protein band as represented on Figure 9.…”
Section: Resultsmentioning
confidence: 99%